Functional design employing miniaturized electronics with wireless signal provision to a smartphone for a strain-based measuring system for ski poles - Hentschel, U.; Steinbild, P. J.; Dannemann, M.; Schwaar, A.; Modler, N.; Schürer, A. (Computers, 2021)
The individual monitoring of cross-country skiers` technique-related parameters is crucial to identifying possible athlete-individual deficits that need to be corrected in order to optimize the athlete`s performance in competition. To be able to record relevant biomechanical parameters during training in the field, the development of measuring systems exploiting the athlete`s full potential is the key. Known mobile monitoring systems for measuring forces on ski poles use comparably heavy uniaxial load cells mounted on the pole with a data logger also attached to the pole or carried by the athlete. Measurements that are more accurate can be acquired using wire-based systems. However, wire-based systems are highly immobile and only usable when the athletes undergo a stationary test, e.g., on a treadmill. This paper focuses on the functional design of a measuring system using specialized, miniaturized electronics for acquiring data from strain sensors. These data are then used to determine the technique-related parameters pole force and angle of bend. The functional design is also capable of transmitting the acquired data wirelessly via Bluetooth to a smartphone that runs a proprietary app. This approach is advantageous regarding mass, dynamic behavior, analyzing functionality, and signal processing compared to the state of the art.